I Won't Make the Same Mistake Again: Burnout History and Job Preferences - Philippe Sterkens; Stijn Baert; Eline Moens; Eva Derous; Joey Wuyts (Institute of Labor Economics (IZA), 2022)
The existing burnout literature has predominantly focussed on the determinants of burnout, whereas its consequences for individual careers have received little attention. In this study, we investigate whether recently burned-out individuals and persons with a very high risk of clinical burnout differ in job preferences from non-burned-out workers. Moreover, we link these differences in preferences with (1) diverging perceptions of job demands and resources in a job, as well as (2) distinct weighting of such perceptions. To this end, a high-quality sample of 582 employees varying in their history and current risk of burnout judged fictitious job offers with experimentally manipulated characteristics in terms of their willingness to apply as well as perceived job demands and resources. We find that recently burned-out employees appreciate possibilities to telework and fixed feedback relatively more, while being relatively less attracted to opportunities for learning on the job. Moreover, employees with a very high risk of burnout are more attracted to part-time jobs. These findings can be partially explained by differences in the perceived resources offered by jobs.
Keywords: J62; I12; C91; C83; 330; burnout; labour market; job search; job preference; factorial survey experiment